Cheddar Cheese Fluoridation and Dental Health - Najim, Najim Hadi (The Iraqi Journal of Veterinary Medicine, 2007)
The main objective of this study was to determine what effect the additionof sodium fluoride would have on the Cheddar cheese quality. Raw milk waspasteurized and separated for three treatments as follows: control, supplementedwith 4 ppm and 40 ppm fluoride. Cheddar cheese was processed for eachtreatment and ripened for 120 days at 7oC and sampled at 60 and 120 days.Analyses performed included both sensory evaluation and gas chromatographywith headspace sampling (GCHS). Under conditions of this study significantP< 0.05 higher mean flavor and body/texture scores were observed in both thecontrol cheese samples and those with 4 ppm added fluoride than those with 40ppm added fluorides.The predominant flavor criticisms in Cheddar cheese treated with 40 ppm addedfluoride after 120 days were flat, lacks flavor and bitter. The predominantbody/texture criticisms noted in Cheddar cheese treated with 40 ppm addedfluoride after 120 days were open, mealy, corky, crumbly, pasty and curdy.GCHS results showed that Acetone, 2- butanone, ethanol, 2-pentanone andpropanol increased significantly (P< 0.05) with aging of the Cheddar cheese.However after 60 days of ripening, the control cheese had significantly (P<0.05) lower Acetone, 2-pentanone and higher ethanol values than the fluoridatedcheese. By 120 days, the control cheese had significantly (P< 0.05) higher 2-butanone values than both treated cheese and higher ethanol than the cheesefluoridated at 40 ppm.